Fibroblast heterogeneity in solid tumors: From single cell analysis to whole-body imaging. (November 2022) - Peltier, Agathe; Seban, Romain-David; Buvat, Irène; Bidard, François-Clément; Mechta-Grigoriou, Fatima
Abstract: Cancer-Associated Fibroblasts (CAFs) represent the most prominent component of the tumor microenvironment (TME). Recent studies demonstrated that CAF are heterogeneous and composed of different subpopulations exerting distinct functions in cancer. CAF populations differentially modulate various aspects of tumor growth, including cancer cell proliferation, extra-cellular matrix remodeling, metastatic dissemination, immunosuppression and resistance to treatment. Among other markers, the Fibroblast Activation Protein (FAP) led to the identification of a specific CAF subpopulation involved in metastatic spread and immunosuppression. Expression of FAP at the surface of CAF is detected in many different cancer types of poor prognosis. Thus, FAP recently appears as an appealing target for therapeutic and molecular imaging applications. In that context, 68 Ga-labeled radiopharmaceutical-FAP-inhibitors (FAPI) have been recently developed and validated for quantitatively mapping FAP expression over the whole-body using Positron Emission Tomography (PET/CT). In this review, we describe the main current knowledge on CAF subpopulations and their distinct functions in solid tumors, as well as the promising diagnostic and therapeutic implications of radionuclides targeting FAP.